L’origine et la signification du glossonyme lingala - Mimpongo , Mpoke (AAeO - Afrikanistik-Aegyptologie-Online, 2025)
This article argues that the names Lingála or Mangála, used as glossonyms, are short-forms or elliptical expressions of mangála má libɔkɔ, or sometimes lingála lí mabɔkɔ, which mean ‘the language of markets’ in Bobangi. The names Lingála or Mangála, in themselves, mean ‘language’ or ‘jargon’ and libɔkɔ means ‘big market’. The present work establishes the limits of alternative hypotheses that have been suggested in the literature, namely (i) that the glossonym Lingala may come from the ethnonym Bangala: erroneous because the Bangála people never existed), (ii) that the names li-ngála/ma-ngála come from the noun mongálá meaning ‘the arm of the river’: mongálá and ma-ngála contain two completely different roots and with different tones in Bobangi, or finally (iii) that the designation of the language with the prefix li- (li-ngála) was an invention of Catholic missionaries: this cannot be, because the language or jargon in question was already called either Bobangi, Mangala or Lingala before colonization. This work draws on historical sociolinguistics as well as the grammar of Bobangi and Lingala to explain the origin and meaning of the glossonym. It gives an account of how Africans named this language before the various glossonyms proposed by Europeans.